The Third International Genomic Medicine Conference (3rd IGMC, 2015): overall activities and outcome highlights. (October 2016) - Abu-Elmagd, Muhammad; Assidi, Mourad; Dallol, Ashraf; Buhmeida, Abdelbaset; Pushparaj, Peter; Kalamegam, Gauthaman; Al-Hamzi, Emad; Shay, Jerry; Scherer, Stephen; Agarwal, Ashok; Budowle, Bruce; Gari, Mamdooh; et al.
Abstract The Third International Genomic Medicine Conference (3rd IGMC) was organised by the Centre of Excellence in Genomic Medicine Research (CEGMR) at the King Abdulaziz University, Jeddah, Kingdom of Saudi Arabia (KSA). This conference is a continuation of a series of meetings, which began with the first International Genomic Medicine Conference (1st IGMC, 2011) followed by the second International Genomic Medicine Conference (2nd IGMC, 2013). The 3rd IGMC meeting presented as a timely opportunity to bring scientists from across the world to gather, discuss, and exchange recent advances in the field of genomics and genetics in general as well as practical information on using these new technologies in different basic and clinical applications. The meeting undoubtedly inspired young male and female Saudi researchers, who attended the conference in large numbers, as evidenced by the oversubscribed oral and poster presentations. The conference also witnessed the launch of the first content fornpj Genomic Medicine, a high quality new journal was established in partnership by CEGMR with Springer Nature and published as part of the Nature Partner Journal series. Here, we present a brief summary report of the 2-day meeting including highlights from the oral presentations, poster presentations, workshops, poster prize-winners and comments from the distinguished scientists.